Improving the sinterability of CeO2 by using plane-selective nanocubes. Issue 14 (November 2019) - Dan, Xiong; Wang, Chao; Xu, Xi; Liu, Ya; Cheng, Xiaowei; Fronzi, Marco; Bi, Lei; Zhao, X.S.
Abstract: CeO2 nanocubes with (100) surface orientation are successfully synthesized and found to facilitate the sinterability of CeO2 material. The CeO2 nanocubes show a much-improved sinterability relative to CeO2 nanoparticles prepared by the conventional citric-nitrate method. The nanocubes can be successfully sintered at a relatively low temperature of 1200 °C without using any sintering aids. In contrast, a pellet using conventional CeO2 nano-powder obtained from the conventional citric-nitrate method can be densified only after sintering at 1400 °C, which is 200 °C higher than that for the CeO2 nanocube sintering, although the starting particle size of both CeO2 samples is similar. Density functional theory indicates that the surface energy of the (100) plane is significantly higher than that of the (111) plane, which is the more typical surface presentation of conventional CeO2 particles. This high surface energy allows fast growth of the CeO2 nanocubes during sintering, contributing to their improved sinterability.